DESTRUCTURING AND SOCIAL CONFLICT: A LONG-TERM STUDY OF THE VALLEY OF CATAMARCA FROM A MULTIDISCIPLINARY PERSPECTIVE: un estudio de larga duración del Valle de Catamarca en perspectiva multidisciplinaria - Fonseca, Ezequiel; Fiant, Roxana; Puentes, Hugo (Centro de Estudios de Arqueología Histórica (CEAH) de la Universidad Nacional de Rosario, 2024)
This paper deals with the valley of Catamarca (Province of Catamarca, Argentina) as a material expression of a landscape built over time, accounting for a long cultural history. We focus on a period that begins around 200 AD and extends up to the time of the Spanish conquest in the 16th century, a situation that deconstructed the social order of the local population, modifying their relationship with the landscape. An example of this can be seen through the recognition in the archaeological record of the Averías ceramic style, typical of the Chaco region, associated with Spanish materials that refer to situations of relocation.We seek to produce a multidisciplinary perspective in which archaeology, history and critical geography stimulate problematisation by focusing attention on the processes of destructuring and social conflict involved in the valley. To this end, we carry out a long-term analysis on a local/regional scale, linking the objectification of social practice, a practice which in turn is imprinted on the material culture as a lived and inhabited space. In this sense, documentary sources are considered, as well as various related historical studies, in articulation with the results obtained from our excavations, considering the convergence between landscape and region as an open, heterogeneous space, and not exactly coinciding with natural and/or political limits.